KINERJA USAHA PENGGILINGAN PADI, STUDI KASUS PADA TIGA USAHA PENGGILINGAN PADI DI CIANJUR, JAWA BARAT - Tursina Andita Putri; Nunung Kusnadi; Dwi Rachmina (Jurnal Agribisnis Indonesia, 2013)
It is assumed that government policy to protect farmer’s income by maintaining a high grain price that leads to a high production cost of  rice milling combine with a policy that keeping the rice at relatively low price to protect consumer, causes a low profit of rice milling business. To prove it, multiple case study was conducted to portray the performance of rice milling business by identifying and analyzing the cost and revenue structure of rice milling business. In this study, three types (maklon, non maklon, and combination of both) of rice milling business were selected. The biggest cost of rice milling business is the cost of purchasing grain, while the main revenue derived from rice. The rice milling business can still tolerate a 9.81 persent increase of the grain price. It is equal to the maximum price of grain Rp 4281,93 per kg GKP. While the decline in the price of rice that can still be tolerated is of 10.34 percent that’s referred to a minimum price of rice Rp 8120.00 per kg. The largest proportion of the rice milling business profit is not derived from rice as main product but from the by product such as rice bran, rice husk, broken rice, and groats. Type of businees, price of inputs and outputs, and by-product management would be the key variables that determine the business performance. These variables should be more studied in the future research.